Sexual orientation and psychotic-like experiences among Chinese college students: the role of gender - Lu, Dali; Qing, Zaihua; Tu, Ying; Liu, Xiaoqun (Frontiers in Psychiatry, 2023)
Objective: The mental health of sexual minorities have received increasing attention, but there are few studies on the risk of psychotic-like experiences (PLEs) among sexual minorities. The purpose of this study is to explore the relationship between different sexual orientation and PLEs among college students and the moderating effect of gender. Methods: 4460 college students from 7 provinces participated in this cross-sectional survey. Chi-square test and logistic regression were used to investigate the relationship between sexual orientation and PLEs. Results: Of the participants, 4.9% identified themselves bisexual, 1.1% as Lesbian/gay, and 5.6% were questioning/unsure; 60.1% of the sample experienced at least one PLEs item, 59.2 % delusional experiences (DEs), and 20.6 % hallucinatory experiences (HEs). Compared with heterosexual college students, bisexual and questioning students showed higher risk of PLEs, DEs and HEs, and Lesbian/Gay students showed higher risk of HEs. Stratified analysis indicated that sexual orientation was significantly associated with PLEs only for female college students. Conclusions: Sexual orientation was predictive factor of PLEs. In particularly, different sexual minority subgroups show the different effects on PLEs between male and female college students. Mental health interventions about PLEs could take distinct strategies based on different sexual orientation and the gender disparity.